Events associated with stability and change in adult locus of control orientation over a six-year period. (1st May 2018) - Nowicki, Stephen; Ellis, Genette; Iles-Caven, Yasmin; Gregory, Steven; Golding, Jean
Abstract: Although locus of control (LOC) has been the focus of thousands of studies we know little about how or if it changes over time and what is associated with change. Our lack of knowledge stems in part from the past use of cross-sectional and not longitudinal methodologies to study small numbers of participants from non-representative populations. The purpose of the present study was to use a longitudinal design with a large representative population to provide relevant information concerning the stability and change of adult LOC. Before the birth of their child, and again six years later, mothers and their partners participating in the Avon Longitudinal Study of Parents and Children (ALSPAC) completed LOC tests and structured stressful events surveys. Analyses revealed that stresses experienced in relationships with spouses, friends and family, financial stability and job security, and illness/smoking were associated with changes in LOC. Results suggest substantial variation of LOC within spousal/parent dyads and moderate stability of LOC over time for both men and women. Stressors associated with change in LOC may be possible candidates when considering interventions to modify LOC expectancies. Highlights: Little is known as to factors associated with changes in LOC over time. This is a unique data set measuring LOC in men and women over a 6 year period. Results show relationship stressors were associated with change in LOC orientation. Stressors could be candidates when considering interventions to modify LOC. Substantial variation of LOC within spousal dyads was found.